STRATEGI AIRISH HOTEL DALAM MENGHADAPI TANTANGAN INDUSTRI PERHOTELAN MODERN - Oka Suci Wulandari; M. Mifta Farid (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
The current hospitality industry faces various challenges, including high levels of competition, the rapid development of digital technology, and the dynamics of changing consumer behavior. This situation encourages hotels to develop adaptive and innovative strategies to maintain and enhance competitiveness. This study aims to examine the strategies implemented by Airish Hotel Palembang in responding to the challenges of the modern hospitality industry. This research used a descriptive qualitative method, with data collection techniques through observation, interviews, and documentation conducted during the Student Experience Program within the Merdeka Belajar Kampus Merdeka (PPM MBKM) framework. The research findings indicate that Airish Hotel Palembang implements a digital marketing strategy by utilizing social media and collaborating with online booking platforms, along with efforts to improve service quality and strengthen brand awareness. The implementation of this strategy is considered effective in expanding market reach and enhancing the hotel's competitiveness. Therefore, a digital technology-based marketing and service strategy is crucial for Airish Hotel Palembang in facing the challenges of the modern hospitality industry.